Economic Mechanism of the Region Food Security Under Slope Agriculture - Паленичак, О. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
At the present stage of national economy agricultural sector development the economic mechanism of food security plays particularly important role. Foreign experience shows the need for an integrated their applications; providing economic and social effects the implementation of these measures. The study is to justify the need for economic governance of the region food security mechanisms in terms of slope farming. A study of the economic mechanisms for the management of food security in the region should contribute to improving the pricing mechanism on the food market by simultaneous application of state regulated prices for agricultural products and foodstuffs that have substantial social significance. The article discusses current issues using economic mechanisms to control food security in terms of slope agriculture with the respective legal provision. The necessity of firm trade of agricultural enterprises based on its own small processing and by processing raw materials in large processing plants was substantiated. In special eco-products stores; food-staffs grown in slope farming; and environmentally clean areas can be realized at higher prices. Using a price premium (1-10%) for relevant products will form a monetary fund to offset the cost of production; which will be acquired socially unprotected citizens of districts in which agricultural land is located on sloping lands and are characterized by relatively low levels of fertility.